Patterns of Economic Transition and Structural Adjustments - Amit Bhaduri (The Vienna Institute for International Economic Studies (wiiw), 1994)
Economic liberalization is premised usually on the assumption that the private sector would spearhead the process of required structural adjustments. However, since in no economy the private sector operates in isolation, it is necessary to specify the patterns of economic interaction between the private and the public sector under which this may be feasible. This paper attempts to provide a formal framework to examine this problem and, explores how issues like public investment an infrastructure and the regime of property rights can be dealt with analytically during the process of economic transition and structural adjustments.
Keywords: 330; Economic transition; structural adjustment; property rights; evolutionary biology; public and private sector interaction